Intrinsic Immune Response of HBV/HDV-Infected Cells and Corresponding Innate (Like) Immune Cell Activation - Christopher Groth; Svea Wupper; Gnimah Eva Gnouamozi; Katrin Böttcher; Adelheid Cerwenka (Livers)
Infection of hepatitis B (HBV) patients with hepatitis D (HDV) can cause the most severe form of viral hepatitis, leading to liver fibrosis, liver failure, and hepatocellular carcinoma. HDV relies on simultaneous infection with HBV for the generation of infectious viral particles. The innate immune response, which is weakly induced in HBV infection, becomes strongly activated upon HDV co-infection. In HBV/HDV co-infection, the immune system comprises a cell-intrinsic strong IFN response, which leads to the induction of interferon-stimulated genes (ISGs), the local activation of liver-resident innate immune cells, and additional immune cell recruitment from the blood. Efficient innate immune responses are indispensable for successful viral control and spontaneous viral clearance. Despite this fact, innate immune cell activation can also contribute to adaptive immune cell inhibition and accelerate liver damage in HBV/HDV infection. While the intrinsic IFN response in HDV-infected cells is well characterized, far less is known about the cellular innate immune cell compartment. In this review, we summarize HBV/HDV replication characteristics and decipher the role of innate immune cell subsets in the anti-viral response in HBV/HDV infections. We further review the impact of epigenetic and metabolic changes in infected heptatocytes on the innate anti-viral response. Moreover, we discuss the potential of exploiting the innate immune response for improving vaccination strategies and treatment options, which is also discussed in this review.